Shrek the musical - James, Brian D'Arcy; Foster, Sutton 1975-; Sieber, Christopher; Breaker, Daniel; Tartaglia, John (DreamWorks Animation [u.a.], 2013)
The greatest fairy tale never told comes to life as never before in Shrek The Musical, the highly acclaimed Broadway production based on the smash-hit movie. Featuring a fantastic score of seventeen all-new songs, along with unforgettable characters and outrageous humor, it's ogre-sized fun for the whole family
Interpr.: Brian d'Arcy James; Sutton Foster; Christopher Sieber; Daniel Breaker; John Tartaglia. - Enth. Bonusmaterial: Songbook with 7 sing-alongs
Keywords: DVD-Video